Mucosal bacteria as a modern biological indicator of Tigris River pollution in the city of Baghdad (Journal of the College of Basic Education, 2022)
This study was conducted to investigate the agricultural pollution in the waters of the Tigris River in the city of Baghdad for three modeling areas (north, middle and south) for the period from 1/1 to 30/9 of the year 2011, by searching for the presence of a group of mucosal bacteria of both types, cellulosic and bacteriolytic, as well as conducting Other routine bacteriological tests (total number of bacteria, coliform group, fecal coliforms, streptococci and fecal streptococci) as well as physical and chemical tests of water (temperature, turbidity, vital oxygen requirement and pH). The results were as follows: